2009
DOI: 10.1099/vir.0.007518-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of antiviral and proinflammatory cytokines and suppression of Fas-mediated apoptosis by NS1 of H9N2 avian influenza virus in chicken macrophages

Abstract: The NS1 protein is known to suppress immune responses in influenza virus-infected hosts. However, the role of NS1 in apoptosis in infected cells is disputed. In this study, through the use of a mutant A/pheasant/California/2373/1998 (H9N2) avian influenza virus (AIV) with a truncated NS1, we have demonstrated that a functional NS1 protein suppresses the induction of interferons in chicken macrophages. However, NS1 appeared to be irrelevant to the regulation of cytokines interleukin (IL)-1β and IL-6, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…It was shown previously that some of the TNF family members are upregulated in H9N2-infected HTC cells, triggering the extrinsic apoptotic pathway (Xing et al, 2009). In H9N2-infected cells, 15-and 25-fold increases in FasL transcripts were detected at 8 and 16 h p.i.…”
Section: Erk Suppresses Tnf-family-mediated Extrinsic Apoptosis In H9mentioning
confidence: 74%
See 3 more Smart Citations
“…It was shown previously that some of the TNF family members are upregulated in H9N2-infected HTC cells, triggering the extrinsic apoptotic pathway (Xing et al, 2009). In H9N2-infected cells, 15-and 25-fold increases in FasL transcripts were detected at 8 and 16 h p.i.…”
Section: Erk Suppresses Tnf-family-mediated Extrinsic Apoptosis In H9mentioning
confidence: 74%
“…We have observed that the HTC cells underwent aggressive apoptosis in response to H9N2 infection (Xing et al, 2008b(Xing et al, , 2009). However, in HTC cells treated with U0126 (10 mM), we found that apoptosis was more pronounced than in untreated controls at various time points p.i.…”
Section: Erk Suppresses Tnf-family-mediated Extrinsic Apoptosis In H9mentioning
confidence: 99%
See 2 more Smart Citations
“…The full biological consequences of NS1-mediated PI3K activation are far from clear, although an association with regulating lung epithelium ion channel activity has been proposed (11). Early studies also suggested that NS1-activated PI3K contributes to the suppression of cellular apoptosis during virus infection (12)(13)(14)(15), but very recent data now indicate that this may not be the case (16). Thus, the precise role of this important signaling pathway with respect to the influenza A virus replication cycle has yet to be firmly established.…”
mentioning
confidence: 99%